Adoption of principle-based IFRS and intercompany comparability of operating performance - Protap Kumar Ghosh; Ranajit Kumar Bairagi; Abinash Mondal (Asian Journal of Accounting Research, 2020)
The study aims to investigate whether the adoption of IFRS could ensure ultimate intercompany comparability of operating performance in terms of uniformity in the application of accounting methods and reporting style.Using content analysis on 125 annual financial statements of 25 companies from five industries listed on the Dhaka Stock Exchange in Bangladesh, this study reports that only the sole adoption and application of principle based IFRS cannot ensure ultimate intercompany comparability of financial reports.The findings document that the adoption of IFRS cannot ensure the application of same accounting methods as well as way of presentations which is a precondition of greater comparability of operating performance of competitive firms. The methodological and reporting direction through local regulatory agencies alongside maximum compliance with principle based IFRS can enhance intercompany comparability of financial reports in the same industry.This study tries to manifest that sole adoption cum implementation of IFRS could not ensure ultimate intercompany comparability of operating performance within the same industry and urges to conduct further research to find out the ways to do so.